KORELASI KEJADIAN LOW BACK PAIN TERHADAP BERAT BEBAN KERJA PADA PEKERJA PEMETIK TEH DI PTPN VI KAYU ARO - Jefri Henky; Eko Perdana Putra; Nabilah Luthfianazla (Nusantara Hasana Journal, 2026)
Low back pain (LBP) is a very common health problem that can limit activity. There are several risk factors can influence the incidence of LBP, including individual characteristics such as age, gender, height, and bodyweight. In addition, occupational factors such as workload weight and work position can increase the risk of LBP. The weight of the load lifted can affect workers' health, such as causing pain or injury to the back. This study aims to determine the correlation between workload weight and the incidence of LBP among tea pickers at PTPN VI Kayu Aro. This type of research is a correlative analytic with a prospective cohort study design, with 62 samples using a consecutive sampling technique. Data collection was carried out by conducting interviews and assessing the work positions of tea pickers with the OWAS assessment form. Univariate data analysis is presented in the form of frequency distributions and percentages, while bivariate data analysis uses a contingency correlation test using the SPSS program version 22.0. Based on the results of the study, the most common age group is 36-45 years old, amounting to 22 people (35.5%), the most common gender is female, amounting to 46 people (74.2%), the average height is 167 cm, the average weight is 54 kg, as many as 46 people (74.2%) lift heavy category loads, the most workers work in category 2 work positions, namely 52 people (83.9%), most tea pickers experience LBP, namely 52 people (83.9%), there is a relationship between the weight of the workload and the incidence of LBP in PTPN Kayu Aro tea pickers with p value = 0.007 (p<0.05).